Aerobic activity significantly reduces blood pressure among hypertensive adults in Africa: a systematic review and meta-analysis - Leeyio, Titus Robert; Katto, Nicholas Philip; Juma, Faiza Mohamed; Mkassy, Farida Iddy; Liwa, Anthony Cuthbert; Matuja, Sarah Shali; Byamungu, Daniel; Ayieko, Philip; Bintabara, Deogratius; Konje, Eveline Thobias (Frontiers in Public Health, 2025)
BackgroundSub-Saharan Africa is faced with the increasing prevalence of high blood pressure, with projections estimating that 216.8 million people will be affected by 2030. Aerobic activity has been recognized for its cardiovascular benefits. However, its effect remains under-explored, and the findings are largely inconsistent. Therefore, this review aimed to estimate the overall effect of aerobic activity on blood pressure among hypertensive adults receiving medication in Africa.MethodsRandomized clinical trials conducted in Africa and published between 2000 and September 2024 were considered eligible if they included hypertensive adults aged 18 years and older. Studies were identified through searches on PubMed, African Journal Online, Hinari, and Science Direct databases. In addition, the Cochrane risk-of-bias tool (ROBIS-2) was used for quality assessment.ResultsOf the 683 articles identified, eight qualified for qualitative assessment, comprising 1,112 participants on antihypertensive medication (625 in the intervention group and 487 in the control group). The follow-up duration ranged from 6 to 16 weeks, with different aerobic modalities such as brisk walking, dance, and bicycle ergometer. These activities were performed either continuously or at different time intervals (three times per week), lasting between 30 and 60 min. The overall risk of bias was moderate, and the intensity of the training was based on VO2Max (64–79%) and VO2Peak (40–79%). The main findings suggest a significant pooled reduction in systolic blood pressure, with a mean difference (MD) of 5.40 mmHg [95% CI: −9.05 to −1.75], and a modest reduction in diastolic blood pressure, with an MD of 1.90 mmHg [95% CI: −3.81 – 0.01]. Subgroup analysis revealed that interventions lasting for at least 8 weeks produced stronger effects than those implemented for more than 8 weeks.ConclusionOur finding shows that adherence to antihypertensive medications in addition to aerobic activity effectively reduced blood pressure among hypertensive adults in Africa, particularly at 8 weeks, with a slightly diminished effect in prolonged durations. It is, therefore, imperative to conduct further studies in this area of hypertension management.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024614250.